Psychosocial Risk Pathways from Childhood Sexual Abuse to Intimate Partner Violence among Sexual Minority Men: A Test of the Psychological Mediation Framework of Minority Stress - Berke, Danielle S. (Journal of interpersonal violence, 2023)
Although sexual minority men experience elevated rates of childhood sexual abuse (CSA) and equal or greater rates of intimate partner violence (IPV) victimization compared to heterosexual individuals, little research has examined mechanisms linking these forms of victimization in this high-need population. We examined general (i.e., emotion regulation difficulties) and sexual minority specific (i.e., internalized homophobia) mediational pathways between CSA and IPV victimization in a longitudinal sample of 940 sexual minority men. Path analyses revealed significant associations between CSA and internalized homophobia, between internalized homophobia and emotion regulation difficulties, and between emotion regulation difficulties and IPV victimization. No indirect effects of CSA on IPV via general or minority specific pathways were observed. Findings suggest that minority stress specific (i.e., internalized homophobia) and general psychological risk factors (i.e., emotion regulation difficulties) co-occur and may function along independent pathways to link CSA to IPV revictimization. Future work is needed to investigate how mitigation of these modifiable pathways may be targeted to inform violence prevention interventions for sexual minority men.